Telecommunications quality of service management from legacy to emerging services - Oodan, A. P. (Antony P.); Ward, Keith E.; Savolaine, Catherine G.; Daneshmand, Mahmoud; Hoath, Peter (London, United Kingdom Institution of Engineering and Technology, 2003)
The following topics are dealt with: quality of service in telecommunications; viewpoints of quality of service; customers' quality of service requirements; quality of service offered/planned by the service provider; quality of service delivered by the service provider; customer's perception of quality of service; network evolution and its performance; network performance engineering of legacy networks; Internet, Internet services and quality of service framework; quality of service for real-time internet applications; quality of service for non-real-time Internet applications; quality of service in mobile communication systems; quality of service of satellite communications; service surround and customer relationship management; number and billing; ergonomic considerations in the design of products and services; telecommunication services for people with disabilities; role of consumer and user groups; role of regulation; role of standards; comparisons of performance; economics of quality of service; telecommunications security; telecommunications fraud and architectural framework for study of quality of service.
Previous ed. published as: Quality of service in telecommunications / by A.P. Oodan, K.E. Ward and A.W. Mullee. 1997.
Electronic reproduction.
Keywords: Telecommunication -- Customer services; Telecommunication -- Quality control; Electronic books